Optimization of the direct buried characteristics for 11kV underground cable installation - Raveendran S.K.; Arokiam D.; Thevadass M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Energy utilization; Telecommunication cables; Underground cables; Cable ampacity; Cable installations; Direct Buried; Installation methods; Insulation materials; Operational lifetime; Underground cable systems; Underground power cable system; Cables